Influence of Low-Dose Alcohol Consumption on Post-Ischemic Inflammation: Role of Cystathionine γ-Lyase - McCarter, Kimberly D. (Alcohol, 2018)
Low-dose alcohol consumption (LAC) has been shown to suppress post-ischemic inflammation and alleviate cerebral ischemia/reperfusion (I/R) injury. Cystathionine γ-Lyase (CSE) is one of the enzymes that endogenously produce hydrogen sulfide (H(2)S), which has an anti-inflammatory property at low concentration. We determined the potential role of CSE in the protective effect of LAC. Male C57BL/6J mice were divided into two groups, an ethanol group and a control group, and gavage fed with 0.7 g/kg/day ethanol or volume-matched water once a day for 8 weeks. Transient focal cerebral ischemia was induced by unilateral middle cerebral artery occlusion (MCAO) for 90 minutes. CSE inhibitors were intraperitoneally given 30 minutes prior to the ischemia. Cerebral I/R injury, H(2)S production, adhesion molecules, IL-1 receptor accessory protein (IL-1RAcP), IL-1β, microglial activation, and neutrophil infiltration were evaluated at 24 hours of reperfusion. Eight-week ethanol feeding upregulated CSE in the cerebral cortex and reduced cerebral I/R injury. Moreover, ethanol increased post-ischemic H(2)S production and alleviated the post-ischemic inflammatory response (expression of adhesion molecules, IL-1RAcP, IL-1β, microglial activation, and neutrophil infiltration) in the peri-infarct cerebral cortex. Both inhibitors of CSE, DL-Proparglyglycine (PAG) and β-cyano-L-alanine (BCA), abolished the protective effect of ethanol on cerebral I/R injury. In addition, PAG attenuated the inhibitory effect of ethanol on the post-ischemic inflammation. Thus, LAC may protect against cerebral I/R injury by suppressing post-ischemic inflammation via an upregulated CSE.